2020
DOI: 10.3390/nu12092810
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Thiamine Evaluation in a Practical Setting

Abstract: Thiamine is a crucial cofactor involved in the maintenance of carbohydrate metabolism and participates in multiple cellular metabolic processes. Although thiamine can be obtained from various food sources, some common food groups are deficient in thiamine, and it can be denatured by high temperature and pH. Additionally, different drugs can alter thiamine metabolism. In addition, the half-life of thiamine in the body is between 1 and 3 weeks. All these factors could provide an explanation for the relatively sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 117 publications
(191 reference statements)
0
31
0
2
Order By: Relevance
“…It should be stated that thiamine losses in the dried vegetables analyzed were not high. Thiamine is one of the most labile vitamins [ 9 , 12 , 31 , 38 , 39 , 40 ]. The analysis of Japanese cooking meals have shown 50% losses of thiamine on average.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be stated that thiamine losses in the dried vegetables analyzed were not high. Thiamine is one of the most labile vitamins [ 9 , 12 , 31 , 38 , 39 , 40 ]. The analysis of Japanese cooking meals have shown 50% losses of thiamine on average.…”
Section: Discussionmentioning
confidence: 99%
“…The values of half-life thiamine periods indicate that the lower the temperature of storage, the lower the dynamics of thiamine loss. Earlier studies showed that most chemical compounds are increasingly active at higher temperatures [[ 9 , 48 , 49 ]]. Thiamine is one of the most labile vitamins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations